PEMANFAATAN HASIL PERIKANAN SEBAGAI PRODUK BERNILAI TAMBAH (VALUE-ADDED) DALAM UPAYA PENGANEKARAGAMAN PANGAN [Utilization of Fishery Products with Added Value to Support Food Diversification] Tri Winarni Agustini 1) , dan Fronthea Swastawati 1) 1) Staf Pengajar Program Studi Teknologi Hasil Perikanan Jurusan Perikanan FAPRIKAN, Universitas Diponegoro – Semarang Diterima 12 Agustus 2002 /Disetujui 8 April 2003 ABSTRACT Utilization of fishery products efficiently and cooperatively is important - Tri Winarni Agustini; Fronthea Swastawati (Jurnal Teknologi dan Industri Pangan, 2003)
PEMANFAATAN HASIL PERIKANAN SEBAGAI PRODUK BERNILAI TAMBAH (VALUE-ADDED) DALAM UPAYA PENGANEKARAGAMAN PANGAN [Utilization of Fishery Products with Added Value to Support Food Diversification] Tri Winarni Agustini 1) , dan Fronthea Swastawati 1) 1) Staf Pengajar Program Studi Teknologi Hasil Perikanan Jurusan Perikanan FAPRIKAN, Universitas Diponegoro – Semarang Diterima  12 Agustus 2002 /Disetujui 8 April 2003 ABSTRACT   Utilization of fishery products efficiently and cooperatively is important to improve esthetical value of the products. Diversification of fishery products is possible to be implemented, both vertically and horizontally. Understanding of their processing technology is very important for fish processors in order to produce healthy products and highly accepted by consumers. In accordance to the government policy about National Food Safety Programs, one of which is to improve the production of processed food, the diversification of fishery processing should be pointed to very focus condition. The consumption of fish is still low in Indonesia (± 21.69 kg per capita per year), while the fishery resources are abundance. Therefore, efforts in increasing consumption of fish by the consumer to reach the target of the national program i.e. 26.5 kg/capita/year are needed.  Production of “Value-added” by diversification method is aimed not only to improve consumption but also to create appetizing products for the consumers. Some examples of “Value Added” product that are becoming popular nowadays include: fish ball, milk fish pressed-cooked, fish nuggets, fish sausage, ekado fish, aji furai, etc. Some products had been sold by home industries but is still possible to produce in industrial scale. The raw material used can be from marine or cultured fish and also frozen surimi, that are potential to be implemented in Indonesia.